37.7k views
0 votes
4p squared + 7q cubed. p=-3
q= -2​

User Vieux
by
5.1k points

2 Answers

6 votes

Answer:

-20

Explanation:

4p^2 + 7q^3

4(-3)^2 + 7(-2)^3

4(9)+7(-8)

36 - 56 = -20

User Samir Rahimy
by
5.7k points
4 votes

For this case we have the following expression:


4p ^ 2 + 7q ^ 3

We must find the value of the expression when:


p = -3\\q = -2

Substituting we have:


4 (-3) ^ 2 + 7 (-2) ^ 3 =\\4 (9) +7 (-8) =\\36-56 =

Different signs are subtracted and the sign of the major is placed:


36-56 = -20

Answer:

The value of the expression is -20

User Yordan Nikolov
by
5.5k points